2021
DOI: 10.3390/ijms22042045
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicle-Derived microRNAs of Human Wharton’s Jelly Mesenchymal Stromal Cells May Activate Endogenous VEGF-A to Promote Angiogenesis

Abstract: Despite low levels of vascular endothelial growth factor (VEGF)-A, the secretome of human Wharton’s jelly (WJ) mesenchymal stromal cells (MSCs) effectively promoted proangiogenic responses in vitro, which were impaired upon the depletion of small (~140 nm) extracellular vesicles (EVs). The isolated EVs shared the low VEGF-A profile of the secretome and expressed five microRNAs, which were upregulated compared to fetal dermal MSC-derived EVs. These upregulated microRNAs exclusively targeted the VEGF-A gene with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…We reported that exosomes from BM and WJ showed better angiogenic properties than AD. These results were in line with the previously published reports where WJ and BM have been shown to exhibit enhanced angiogenetic potential [ 55 , 58 ]. However, there are reports that AD-MSCs can promote angiogenesis by increasing endothelial cell differentiation and cell migration [ 59 ], while BM-MSCs express VEGF that promotes angiogenesis [ 60 ].…”
Section: Discussionsupporting
confidence: 93%
“…We reported that exosomes from BM and WJ showed better angiogenic properties than AD. These results were in line with the previously published reports where WJ and BM have been shown to exhibit enhanced angiogenetic potential [ 55 , 58 ]. However, there are reports that AD-MSCs can promote angiogenesis by increasing endothelial cell differentiation and cell migration [ 59 ], while BM-MSCs express VEGF that promotes angiogenesis [ 60 ].…”
Section: Discussionsupporting
confidence: 93%
“…THBS1 is a member of the matricellular protein family that is important in the control of extracellular matrix (ECM) remodelling and has also been reported to promote the proliferation and migration of mesenchymal cells through modulating TGFb activation or protecting the degradation of PDGF (66,67). There are many studies on the MSC-secreted THBS1 in regulating angiogenesis, but rarely on its immunoregulatory function in MSCs (68,69). Marie Maumus and colleagues reported that THBS1 secreted by adipose-derived MSCs may play a protective role in a collagen-induced osteoarthritis (CIOA) mouse model by chondroprotective effects and anti-inflammatory effects on T lymphocytes (70).…”
Section: Discussionmentioning
confidence: 99%
“…The exact paracrine mechanism affecting HUVEC tube formation by hASCs, whether it be a secretory molecule or occurs via extracellular vesicle (EV) secretion, was not evaluated in this study and should be analyzed in more detail in the future. In a previous study by Cinnici et al [ 73 ], MSC-secreted EVs were studied and found to be a crucial part of releasing proangiogenic molecules, leading to increased vascularization. In addition to the culturing conditions, these paracrine properties can be affected by the transplantation mechanisms and better results have been shown with the local administration of mesenchymal stromal cells instead of systemic exposure [ 74 ].…”
Section: Discussionmentioning
confidence: 99%